Controlling the folding of conjugated polymers at the single molecule level via hydrogen bonding. Issue 7 (16th January 2017) - Shao, Beiyue; Zhu, Xinju; Plunkett, Kyle N.; Vanden Bout, David A.
Abstract : In this manuscript, we report a design strategy to control polychromophore polymer folding at the single molecule level through hydrogen-bonding (H-bonding) interactions. Abstract : In this manuscript, we report a design strategy to control polychromophore polymer folding at the single molecule level through hydrogen-bonding (H-bonding) interactions. Polymers composed of bis(2-ethylhexyl)- p -phenylene vinylene (BEH-PPV) oligomers (trimers) containing H-bonding capable side-chains ( e.g., carboxylic acid or urea units) were prepared by copolymerization with flexible linkers. Control polymers with masked H-bonding side-chains ( e.g., t -butyl ester) were also prepared. Different polymer folding schemes are proposed including random or non-folding for the control polymers, and side-on and face-on geometries for the carboxylic acid and urea motifs, respectively. Single molecule excitation polarization spectroscopy demonstrates that the highest folding order is achieved with the urea containing side-chains and isotropic folding is found in polymers that do not contain H-bonding units. We propose that the effects of the chromophore conformational geometries and the type of H-bonding are additive and lead to highly aligned urea-containing polymers. In addition, an examination of the individual polymers' spectral signatures via single molecule spectroscopy showed an overall red-shift of ∼0.06 eV in the 0–0 origin peak for the urea-containing polymer compared to the other two polymer systems. This spectral shift is attributed to planarization of the backbone and further supports the presence of a highly ordered urea-containing polymer structure. Utilization of this H-bonding inclusion synthetic strategy to control polymer secondary structure could provide important design elements for future functional material design.